Association of oily fish intake, sex, age, BMI and APOE genotype with plasma long-chain n-3 fatty acid composition. Issue 1 (6th May 2018) - Fisk, Helena L.; Irvine, Michael; Miles, Elizabeth A.; Lietz, Georg; Mathers, John C.; Packard, Chris J.; Armah, Christopher K.; Kofler, Bettina M.; Curtis, Peter J.; Minihane, Anne M.; Calder, Philip C.
Abstract: n -3 Fatty acids are associated with better cardiovascular and cognitive health. However, the concentration of EPA, DPA and DHA in different plasma lipid pools differs and factors influencing this heterogeneity are poorly understood. Our aim was to evaluate the association of oily fish intake, sex, age, BMI and APOE genotype with concentrations of EPA, DPA and DHA in plasma phosphatidylcholine (PC), NEFA, cholesteryl esters (CE) and TAG. Healthy adults (148 male, 158 female, age 20–71 years) were recruited according to APOE genotype, sex and age. The fatty acid composition was determined by GC. Oily fish intake was positively associated with EPA in PC, CE and TAG, DPA in TAG, and DHA in all fractions ( P ≤0·008). There was a positive association between age and EPA in PC, CE and TAG, DPA in NEFA and CE, and DHA in PC and CE ( P ≤0·034). DPA was higher in TAG in males than females ( P <0·001). There was a positive association between BMI and DPA and DHA in TAG ( P <0·006 and 0·02, respectively). APOE genotype×sex interactions were observed: the APOE 4 allele associated with higher EPA in males ( P =0·002), and there was also evidence for higher DPA and DHA ( P ≤0·032). In conclusion, EPA, DPA and DHA in plasma lipids are associated with oily fish intake, sex, age, BMI and APOE genotype. Such insights may be used to better understand the link between plasma fatty acid profiles and dietary exposure and may influence intake recommendations across population subgroups.